The Effect Of Assessment Of Mean Arterial Pressure And Body Mass Index As Early Detection Of Pre-Eclampsia - Lidia Lushinta; Fara Imelda Theresia Patty; Dini Indo Virawati; Eliza Anggraini (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
Pre-eclampsia or hypertension in pregnancy is a disease that can be detected early so that prevention can be done so that complications do not occur. One way to detect the presence of eclampsia is to carry out early detection using measurements of Body Mass Index (BMI) and blood pressure of pregnant women on a regular basis. Examination of mean arterial pressure in pregnant women with age in the first trimester as a strong predictor in cases of hypertension in pregnancy and preeclampsia. To determine the effect of the assessment of body mass index and mean arterial pressure as early detection of hypertension in pregnancy in the work area of the Trauma Center Health Center, Samarinda City. The method in this study combines two cross-sectional and prospective cohort time approaches. Sampling technique with Accidental Sampling as many as 50 people. Results: The results of this study indicate that there is an effect of MAP and BMI assessment with the incidence of Pre-Eclampsia and Eclampsia with a value (p-value = 0.000 = 0.05). There is an effect of the assessment of Mean Arterial Pressure (MAP) and Body Mass Index with the incidence of Pre-Eclampsia and Eclampsia in the work area of the Trauma Center Health Center in Samarinda City.